2020
DOI: 10.1021/acs.iecr.9b06198
|View full text |Cite
|
Sign up to set email alerts
|

Complete Mineralization of Fluorinated Ionic Liquids in Subcritical Water in the Presence of Potassium Permanganate

Abstract: Reactions of [Me3PrN]­[(CF3SO2)2N] and [C3mpip]­[(CF3SO2)2N] (C3mpip = 1-methyl-1-propylpiperidium) in subcritical water were investigated to develop a technique for recycling fluorine element. By adding KMnO4 to the system, quasi-complete mineralization of the ionic liquids was achieved at 300 °C. When [Me3PrN]­[(CF3SO2)2N] was reacted for 18 h with 158 mM KMnO4, F–, SO4 2–, and NO3 – yields were 98, 98, and 91%, respectively, and the amount of total organic carbon (TOC) was below the detection limit. [C3mpip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…20 To achieve complete mineralization at lower temperature, we examined reactions by oxidative approaches, as described below. 24…”
Section: Reductive Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…20 To achieve complete mineralization at lower temperature, we examined reactions by oxidative approaches, as described below. 24…”
Section: Reductive Approachmentioning
confidence: 99%
“…The figure was prepared from Ref. 24 with permission from American Chemical Society and additional data.…”
Section: Corrected Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…The patterns did not display any diffraction peaks originating from KMnO 4 , while peaks assigned to MnO 2 only were detected. This result is unsurprising because reports on the decomposition of persistent chemicals by treatment with KMnO 4 in superheated water [35][36][37] have indicated that KMnO 4 is converted to MnO 2 (Eq. 4), which then acts as the oxidizing agent.…”
Section: Proposed Reaction Mechanismmentioning
confidence: 99%
“…Furthermore, KMnO 4 , a harmless oxidizing agent, is employed at tap water manufacturing facilities to treat metal compounds, preventing undesired disinfection products (e.g., trihalomethanes) [34]. So far, there have been only three reports that described KMnO 4 -induced superheated water treatment: destructions of acetic acid [35], poly(vinylidene fluoride) [-(CH 2 CF 2 ) n -] [36], and ionic liquids bearing perfluorinated anions [37].…”
mentioning
confidence: 99%